The relationship between body composition and femoral neck osteoporosis or osteopenia in adults with previous poliomyelitis. Issue 2 (April 2015) - Chang, Kwang-Hwa; Tseng, Sung-Hui; Lin, Yu-Ching; Lai, Chien-Hung; Hsiao, Wen-Tien; Chen, Shih-Ching
Abstract: Background: Articles in the literature describing the association between body composition and osteoporosis in subjects with poliomyelitis are scarce. Objective: To assess the relationship between body composition and femoral neck osteoporosis or osteopenia in adults with previous polio. Method: After excluding postmenopausal women, 44 polio (mean age ± standard deviation, 46.1 ± 3.3 years) and 44 able-bodied control volunteers (47.0 ± 4.0 years) participated in the study. Each participant's femoral neck bone mineral density (FNBMD) and whole body composition were measured using dual-energy X-ray absorptiometry. With local reference BMD values of normal young adults installed in the instrument, we obtained T -score values that depended on each FNBMD value. A T -score value of ≤−1.0 indicated decreased T -score, including osteoporosis ( T -score ≤ −2.5) and osteopenia (−1.0 to −2.5). This study conducted logistic regression analyses to find factors associated with osteoporosis and osteopenia. Results: Based on the FNBMD T -score values, 60.0% of middle-aged men with polio had osteoporosis. In adjusted logistic regression analyses, total lean tissue mass (Adjusted odds ratio [95% confidence interval], 0.74 [0.56–0.99], P < 0.05) and male gender (947.16 [6.02–148, 926.16], P < 0.01) were important factors associated with decreased T -score in polio group. Conclusions: Osteoporosis or osteopenia is a common medical problem for middle-aged men with polio. Reduced total lean tissue mass seems to be one of the important factors associated with osteoporosis or osteopenia among subjects with polio. Further research for a clinical tool to assess lean tissue mass for subjects with polio is needed.